Genome sequences of two cold-adapted Cryobacterium spp. SO1 and SO2 from Fildes Peninsula, Antarctica - Teoh, Chui Peng; Wong, Clemente Michael Vui Ling; Lee, D. J. H.; Gonzalez, Marcelo A.; Najimudin, N.; Lee, Ping Chin; Cheah, Yoke Kqueen (Current Science Association, 2018)
Psychrophilic and psychrotrophic bacteria play important roles in nutrient cycling in cold environments. These bacteria are suitable as model organisms for studying cold-adaptation, and sources of cold-active enzymes and metabolites for industrial applications. Here, we report the genome sequences of two Cryobacterium sp. strains SO1 and SO2. Genes coding major proteins related to cold- or thermal-stress adaptations and those with industrial applications found in their genomes are described.